(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Metallo organic compounds can be synthesized electrochemically by anodic generation of metal cations by using sacrificial metal anode. Bis-thiolates complexes of Nickel, Ni(SR)2 have been prepared in an H-type cell by electrochemical oxidation of thiols RSH (ethanethiol, 2-propanethiol, 1-butanethiol, 1-pentanethiol and thiophenol) with sacrificial Nickel (Ni) anode and inert Platinum (Pt) cathode in non-aqueous solution of acetonitrile containing tetrabutylammonium chlorideÂ (as supporting electrolyte). On refluxingÂ Â with ligand (L)Â 2,2’-bipyridyl, these thiolates do not form coordination compounds. However, their adducts Ni(SR)2.L have been synthesized electrochemically by adding the ligand to above thiols in solution phase. All these synthesized complexes have been characterized by elemental analysis, infrared spectral data and other physical measurements. All these compounds are in the solid state with excellent yield and associated with high electrochemical efficiency.